The Spasmolytic, Bronchodilator, and Vasodilator Activities of Parmotrema perlatum Are Explained by Anti-Muscarinic and Calcium Antagonistic Mechanisms - Musaddique Hussain; Hazoor Bakhsh; Shahzada Khurram Syed; Malik Saad Ullah; Ali M. Alqahtani; Taha Alqahtani; Afaf A. Aldahish; Talha Bin Emran; Kashif Ur Rehman; Khalid Hussain Janbaz (Molecules, 2021)
Parmotremaperlatum is traditionally used in different areas of Pakistan to treat gastrointestinal, respiratory, and vascular diseases. This study evaluates the underlying mechanisms for traditional uses of P. perlatum in diarrhea, asthma, and hypertension. In vitro pharmacological studies were conducted using isolated jejunum, trachea, and aortic preparations, while the cytotoxic study was conducted in mice. Crude extract of P. perlatum(Pp.Cr), comprising appreciable quantities of alkaloids and flavonoids, relaxed spontaneously contracting jejunum preparation, K+ (80 mM)-induced, and carbachol (1 µM)-induced jejunum contractions in a concentration-dependent manner similar to dicyclomine and dantrolene. Pp.Cr showed a rightward parallel shift of concentration-response curves (CRCs) of Cch after a non-parallel shift similarto dicyclomine and shifted CRCs of Ca+2 to rightward much likeverapamil and dantrolene, demonstrating the coexistence of antimuscarinic and Ca+2 antagonistic mechanism. Furthermore, Pp.Cr, dicyclomine, and dantrolene relaxed K+ (80 mM)-induced and Cch (1 µM)-induced tracheal contractions and shifted rightward CRCs of Cch similar to dicyclomine, signifying the dual blockade. Additionally, Pp.Cr also relaxed the K+ (80 mM)-induced and phenylephrine (1 µM)-induced aortic contraction, similarly to verapamil and dantrolene, suggesting Ca+2 channel antagonism. Here, we explored for the first time thespasmolytic and bronchodilator effects of Pp.Crand whether they maybe due to the dual blockade of Ca+2 channels and muscarinic receptors, while the vasodilator effect might be owing to Ca+2 antagonism. Our results provide the pharmacological evidence that P. perlatum could be a new potential therapeutic option to treat gastrointestinal, respiratory, and vascular diseases. Hence, there is a need for further research to explore bioactive constituent of P. perlatum as well as further investigation by suitable experimental models are required to further confirm the importance and usefulness of P. perlatum in diarrhea, asthma, and hypertension treatment.